Formation of Anthropometric, Functional and Psychophysiological Indicators in Students of Medical Colleges under the Influence of Physical Activity - Gordiichuk, Svitlana V.; Snikhovska, Irena E.; Harlinska, Alla M.; Hryshchuk, Serhii M.; Chumak, Liudmyla M.; Kalinina, Liudmyla M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
Purpose: to define the dynamics of physical development indicators among medical college students in 2017 and to compare it with the results of the previous study of 2005. Method: The inclusion criteria were: no health complaints at the time of the examination, no chronic diseases in family medical history, no deviations from the norm in clinical and laboratory tests. The selected young men were examined by medical specialists (neuropathologist, ophthalmologist, otolaryngologist, therapist, surgeon); detailed clinical, laboratory and diagnostic tests were conducted: X-ray; spirography; electrocardiography; dental examination; ultrasound examination (cardiovascular, thyroid, abdominal, urological); biochemical blood testing. The participants were subdivided into two groups: Group 1 (students (n=140) who studied at Zhytomyr Medical College in 2004-2005) and Group 2 (students (n=150) who studied at Zhytomyr Medical Institute in 2016-2017). Results: According to the results of studying the dynamics of anthropometric, functional and psychophysiological indicators of physical development among Ukrainian medical college students (n=290; 17-21 years old) in 2017, comparing them with the results of the previous study, conducted in 2005, the tendency to gain in body mass in average values from (0.88 ± 0.26) to (2.7 ± 0.67), in body mass index from (0.88 ± 0.26) to (1.38 ± 0.38), in the fat component from (8.70 ± 0.22) to (9.36 ± 0.21) was established. Conclusions: An increase in body mass index, the fat component in medical college students was revealed, which is related to problems in the quality of the students' diet. Though the muscle mass has increased, and the study indicates that there is insufficient physical activity; sustainability and concentration of attention indicators tend to decrease under the influence of intensification of the educational process. The dynamics of the indicators under analysis indicates the stabilization of the growth process in Ukrainian male students.